Novel Combination for Self-Nanoemulsifying Drug Delivery System of Candesartan Cilexetil - Safa F. Mekhilef; Ahmed A. Hussein (College of Pharmacy University of Baghdad, 2018)
Solubility problem of many of effective pharmaceutical molecules are still one of the major obstacle in theformulation of such molecules. Candesartan cilexetil (CC) is angiotensin II receptor antagonist with very low water solubility and this result in low and variable bioavailability. Self- emulsifying drug delivery system (SEDDS) showed promising result in overcoming solubility problem of many drug molecules. CC was prepared as SEDDS by using novel combination of two surfactants (tween 80 and cremophore EL) and tetraglycol as cosurfactant, in addition to the use of triacetin as oil. Different tests were performed in order to confirm the stability of the final product which includes thermodynamic study, determination of self-emulsification time, particle size and zeta potential measurement, and in-vitro drug release. The results showed that the particle size of the best formula was 13.3 nm and zeta potential of -37.45 mV with approximately 100% release after 45 minutes .These results suggest that the preparation of CC. as SEDDS with the use of the above combination of surfactant and cosurfactant is a promising maneuver for oral delivery of CC. in order to improve its bioavailability.